Equity in the distribution of HELB loans in Kenya in relation to students characteristics: an empirical analysis - Odebero, Stephen O.; Bosire, Joseph N.; Sang, Anthony K; Ngala, Fredrick B. J.; Ngware, Moses W. (Academic Journals, 2007)
Public funding of higher education in Kenya has gone through various stages all buffeted by myriad equity challenges. This prompted the government of Kenya (GoK) to create the Higher Education Loans Board (HELB), through an Act of parliament in the year 1995. GoK guidelines on loan provision to university students emphasise that deserving cases must get support to finance their education depending on their level of need. However, stakeholders have always expressed concern over the manner in which loans are awarded and recovered. These concerns are attributable to the challenges facing HELB loan administration. This study sought to determine the level of equity in the distribution of HELB loans in relation to students’ characteristics. The study used correlational design to determine HELB loan disbursements. The population included all the HELB loan recipients in public and private chartered universities in Kenya who were admitted in the 2000/2001 academic year. Purposive sampling technique was employed in order to select one public rural and one public urban university. Similarly, a private rural and a private urban university were purposively selected. Simple random sampling technique was used to get 626 loan recipients. In order to include non-loan recipients in the sample size, snowball sampling technique was used to get 147 non-recipients. Hypotheses were tested using t-tests and ANOVA at 0.05 level of significance. Results reveal that no statistically significant difference existed between HELB loan disbursements and the students’ characteristics such as gender and location of university. However, the relationship was significant for students’ socio-economic status and programme of study. To enhance fairness in HELB loan disbursements, the study recommends the development of a proper means testing tool that can effectively discriminate students according to their level of need. It also recommends the incorporation in the means testing tool a criteria that considers the cost of the programme, the location of the university and the students’ gender.
Keywords: Equity; finance; higher education; university; means testing; Kenya.